TINJAUAN YURIDIS PERATURAN DAERAH LAMONGAN NO. 12 TAHUN 2010 MENGENAI PAJAK DAERAH ATAS PAJAK RESTORAN SEBAGAI UPAYA PENINGKATAN PENDAPATAN DAERAH LAMONGAN - Sholihan Sholihan; Zuli Kasmawanto; Ahmad Munir (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
Restaurant taxes contribute significantly to local financial revenues. In an effort to increase revenue from the restaurant tax sector, Lamongan District Government implemented the "Eat and Win A Car". The car is claimed as a token of appreciation to the people who eat at restaurants in Lamongan who indirectly contribute to the addition of local income (PAD) Lamongan from restaurant tax. This is because the 10 percent of restaurant tax is charged to the buyer as a taxpayer. The effort of the Bapenda lamongan is claimed to be an effective effort to increase the income from restaurant taxes. The regulation on restaurant tax itself has been regulated in Lamongan Regional Regulation No. 12 Year 2010. This article intends to examine the efforts undertaken by Bapenda Lamongan to increase local revenue through restaurant tax in terms of existing regulations.